MEMBANGUN SERVER VOIP DENGAN ASTERISK DI LINUX BESERTA ADMINISTRASI USER BERBASIS WEBSITE - Setyowibowo, Sigit; ., Syahminan (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
The development of computer network allows for rapid pass voice traffic over computer networks or common called VoIP (Voice Over Internet Protocol). Voice over Internet Protocol (VoIP) is a technology capable of passing voice traffic and video or even a form of data packets over a computer network based on IP (Internet protocol). Major emphasis of VoIP (Voice Over Internet Protocol) is the cost. With two locations that are connected to the internet or network then the conversation becomes very low cost even close to free (Rp0, 00 -). This system is designed using an asterisk on fedora 7 -1.6.0.13Â Keywords : VoIP (Voice Over Internet Protocol)